The craft of college teaching : a practical guide - DiYanni, Robert; Borst, Anton (Princeton University Press, 2020)
The authors provide a guide to the basics of college teaching. Grounded in their own classroom experience, their pedagogical coaching at NYU's Center for the Advancement of Teaching, and their examination of the latest learning science research, it explains how to teach in the college classroom from a learner's perspective-what methods, principles, and activities achieve the best learning outcomes. Chapters address major topics from course and syllabus design to discussion-based teaching, critical reading, and assessment, while brief "interludes" cover various pedagogical elements and applications-including what to do on the first and last days of class and how to incorporate service and experiential learning into curricula. Throughout, the authors provide practical suggestions and strategies, while explaining the underlying pedagogical principles. They also address recent topics that promise to remain fixtures of the educational landscape, such as teaching with technology and teaching in a global context. They steer a middle course on technology, suggesting ways to maximize its benefits while minimizing its distractions. The book coheres around a philosophy of active learning and student engagement. The authors argue that teaching practices should challenge students to think and learn, requiring them to do things with newly acquired knowledge-create models, conduct experiments, debate issues, and more. The authors have enlisted reliable scholarly research to demonstrate that active learning, of the kind they advocate, achieves results: students learn more and better, and their learning is deeper and longer lasting. The authors' pedagogy echoes their epistemology, as they demonstrate how learning and teaching are inextricably intertwined, organic rather than mechanical activities. --